NEW DATA ON TRACE ELEMENT DISTRIBUTION IN CASSITERITE FROM TIN DEPOSITS OF THE RUSSIAN FAR EAST - Khanchuk A.I.; Gorelikova N.V.; Pawlowsky-Glahn V.; Tolosana-Delgado R. (My University, 2004)
The Sikhote Alin accretionary fold system of the Russian Far East incorporates a series of polymineral tin and tungsten deposits that were formed in different geodynamic environments of an active continental paleomargin. The Jurassic-Paleogene evolution of the Far East district was marked by the alternation of the suprasubduction (Andean type) and the transform-shift (Californian type) tectogenesis, which is related to changes in magmatism that promoted the formation of the majority of well-known large tin and tungsten deposits. The analysis of geological data shows that the localization of polygenetic deposits is governed by their relation to continental paleomargin structures with the alternation of subduction and transform environments, which led to the formation of polygenetic mineralization. Geochemical and isotopic data indicate that the sources of the granite magmatism and ore-bearing fluids within this district are heterogeneous.